An Evaluation of the Average Effective Tax Rate Policy for Income Tax Article 21 (A Case Study at KPP Setiabudi Tiga) - Rinda Fitaningsih; Yulianti Abbas (Greenation Research & Yayasan Global Resarch National, 2025)
This study is entitled An Evaluation of the Average Effective Tax Rate Policy for Income Tax Article 21 (A Case Study at KPP Pratama Jakarta Setiabudi Tiga). The research is motivated by the policy issued by the Directorate General of Taxes, which stipulates the use of average effective tax rates as a guideline for withholding Income Tax Article 21 on employment income. The objective of this study is to evaluate the implementation of the average effective tax rate policy based on the evaluation criteria developed by the OECD (2021). This research employs a descriptive qualitative method with a case study approach, using evaluation-type analysis and data collection through interviews and literature review. The results indicate that the application of the average effective tax rate facilitates the tax withholder's calculation of Income Tax Article 21. However, challenges remain regarding taxpayers’ understanding and the tax authority’s dissemination efforts. In conclusion, the policy has proven to be relatively effective in enhancing administrative efficiency and tax compliance, yet it requires further improvement in taxpayer education and regulatory oversight to achieve optimal implementation.